Estudio De La Necesidad De La Adecuación De Servicio Materno Para Mejorar La Calidad De Atención A Las Madres De Los Neonatos Hospitalizados En El Hospital Pediátrico Dr. Francisco De Icaza Bustamante De Guayaquil, En La Ciudad De Guayaquil, Cantón Guayaquil, Provincia Del Guayas” - Carvache Vargas, Betty (2015)
Absenteeism and discomfort of mothers of infants in the NICU area Neonatal Intensive Care Unit at Children's Hospital Dr. Francisco de Icaza Bustamante, in the city of Guayaquil, a problem that affects the growth and physical, emotional development is observed, intellectual and social development of the newborn. Mothers of newborns are assisted in the hospital, mostly belonging to vulnerable groups at high social risk, from urban, rural and marginal areas without support from family and friends. It is the duty of local public and private health encourage breastfeeding, in compliance with the provisions: Health is a right guaranteed by the State, as well as pregnant and lactating women. It is necessary to implement strategies and mechanisms for the efficient care, due to reduced internal users seeking quality care and warmth to the external user, hence, a specific space to bring attention to mothers puerperal state number, identifying Risk factors in infants and determine the social needs of the Department of Neonatology, as a rest area for users and setting rules for the use and commitments; the positive effect when the baby takes the breast of his mother, receives not only the ideal food for growth but receives heat, tactile stimulation, visual, olfactory, gustatory and oral. Contact brings benefits to the sensory system is more mature in the first months of life, and captures the love and support of the mother, developing confidence and self-assurance, so surveys was applied to women in puerperal state, family and companions in number 60, whose results led the adequacy of a living accommodation to provide care for mothers of newborns, also educational talks, to ensure the overall health of mother and child at the hospital regularly offer pediatric "Dr. Francisco de Icaza Bustamante"